Fluorinated azobenzenes as supramolecular halogen-bonding building blocks - Nieland, Esther; Weingart, Oliver; Schmidt, Bernd M. (Beilstein Journal of Organic Chemistry, 2019)
ortho-Fluoroazobenzenes are a remarkable example of bistable photoswitches, addressable by visible light. Symmetrical, highly fluorinated azobenzenes bearing an iodine substituent in para-position were shown to be suitable supramolecular building blocks both in solution and in the solid state in combination with neutral halogen bonding acceptors, such as lutidines. Therefore, we investigate the photochemistry of a series of azobenzene photoswitches. Upon introduction of iodoethynyl groups, the halogen bonding donor properties are significantly strengthened in solution. However, the bathochromic shift of the π→π* band leads to a partial overlap with the n→π* band, making it slightly more difficult to address. The introduction of iodine substituents is furthermore accompanied with a diminishing thermal half-life. A series of three azobenzenes with different halogen bonding donor properties are discussed in relation to their changing photophysical properties, rationalized by DFT calculations.
Keywords: azobenzene; DFT calculations; fluorine chemistry; halogen bonding; photochemistry